The Impact of Interlingual Equivalence on Vocabulary Development. A Case Study on the Acquisition of Specialised (Technical) Lexis - Maria Cristina MIUȚESCU (Scientific Bulletin of the Politehnica University of Timişoara: Transactions on Modern Languages)
This paper explores the correlation between the use of several types of equivalence (e.g., linguistic, paradigmatic, semantic) for ELT purposes and the acquisition of terms and concepts pertaining to the fields of science and technology. It builds on previous research concerning the questionable use of interlingual equivalence (namely foreign language – mother tongue) when seeking vocabulary enhancement on the part of ELLs (English language learners). In order to gain significant insight, mixed research methods have been employed, most notably overt observation carried out among two groups of undergraduates (Architecture and Civil Engineering) paired with assessment strategies.